The South China Sea disputes historical, geopolitical and legal studies - Hsieh, Tsu-Sung (Series on contemporary China, 2018)
The South China Sea Disputes: Historical, Geopolitical and Legal Studies covers various issues regarding the currently controversial theme of the South China Sea (SCS) disputes. It contains insights by scholars mostly from Republic of China (Taiwan), along with ones from Peoples' Republic of China (mainland China), the Philippines, Australia, and the United States (US).The book is divided into three sections, wherein the historical analysis section illustrates certain important but currently neglected treaties for SCS, e.g., the San Francisco Peace Treaty, the Taipei Treaty, and the Cairo Declaration. In particular, the Nationalist government's efforts to recover the Chinese sovereignty in the islands of SCS after the end of World War II are covered. Archival research found in the national archives of the Taiwan, the United Kingdom, the US, and Japan, revealing materials with potential for enhancing territorial and sovereignty claims is covered. In addition, the US State Department historical materials on the SCS disputes are also shown.The geopolitical analysis section in the book specifically addresses the state practice in SCS by Taiwan. It also reveals Taiwan's evolving attitudes from thoughtful planning to perfunctory policy thereof. The circumstances of US-China rivalry in the SCS are also discussed.The legal analysis section includes an explanation of the arbitral award of the SCS, wherein it argues that this arbitration is a non-justiciable dispute resolution. This book serves as a good reference for readers interested in South China Sea disputes.